Fibrotic Tissue and Middle Turbinate Exhibit Similar Mechanical Properties. Is Fibrosis a Solution in Nasal Polyposis? - Luciano Gregório; Rogério Pezato; Rafael Souza Felici; Eduardo Macoto Kosugi (International Archives of Otorhinolaryngology, 2017)
Abstract